USE OF REVERSE LATERAL ARM FLAP FOR COVERAGE OF ELBOW IN BURN PATIENTS - Ashfaq, Faisal (Journal of Ayub Medical College Abbottabad, 2014)
Background: Flap coverage is superior to graft for elbow defects secondary to burns to preserve range of motion. Reverse lateral arm flap is one of the few local options available with good colour and contour match and no sacrifice of major blood vessel. There has been few clinical series describing its use. The aim of this study is to describe its usefulness in both acute and post burn deformities for coverage of elbow defects. Methods: Patient’s record with burns and elbow defects covered with this flap was reviewed for this descriptive case series. Results: Six patients; three males and three females, underwent one stage reverse lateral arm flap for elbow defects from February 2012 to March 2013. Two patients had acute electrical burns, one had acute flame burn and three patients had post burn antecubital contractures. All flaps survived completely providing stable coverage and good range of motion after three months. Conclusion: reverse lateral arm flap must be kept in the armamentarium of a plastic surgeon for coverage of elbow defects Keywords: Reverse lateral arm flap, Elbow, Burns, Contracture